Exploring Chemical Basis of Toxicity Reduction for Processed Roots of Stellera chamaejasme L. Using Ultraperformance Liquid Chromatography–Triple Quadrupole Tandem Mass Spectrometry - Wei Yang; Xiaoli Ma; Ludi Wang; Mengmeng Wei; Shuyao Wang; Siyang Wu; Chen Kang; Yingfei Li (International Journal of Analytical Chemistry)
Some herbal medicines are treated with various processing methods to ensure their safe and effective use. However, chemical basis of toxicity reducing for most herbal medicines remains unclear. Stellera chamaejasme L., particularly the root (ruixianglangdu), is toxic. Thus, ruixianglangdu is commonly processed with vinegar or milk to reduce toxicity. Here, with help of multiple-ion monitoring (MIM)-based metabolomics, we comprehensively capture chemical information of ruixianglangdu. Then, 33 differential components between crude drugs and processed products were identified or tentatively characterized by multiple-ion monitoring–information dependent acquiring–enhanced product ion (MIM-IDA-EPI), whose level changed after being processed by vinegar or milk. It was found that flavonoids especially biflavonones could be the important chemical basis of toxicity reduction for processed ruixianglangdu. In addition, some coumarins and lignanoids could also play a role in reducing toxicity. It is believed that MIM-based metabolomics method was valuable for exploring chemical basis of toxicity reduction for processing. The data is critical to further study the mechanism of toxicity reducing for processed ruixianglangdu.